Healing Communication and Religious Coping: Ruqyah as Meaning-Making Practice in Contemporary Islam - Muhamad Hanif Fuadi; Frista Fitriany Ramadhanita (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Religious healing practices continue to shape how Muslim communities interpret illness despite the expansion of modern healthcare systems. Ruqyah is commonly understood as a spiritual ritual or religious intervention, while its role as a therapeutic communicative practice of meaning-making remains underexplored. This article examines ruqyah as a form of religious coping that operates through healing communication in contemporary Islamic contexts. Using a qualitative literature-based approach through an integrative and thematic interpretive review, this study analyzes scholarly works on religious coping, Islamic spiritual healing, and the relationship between religion and modernity. The analysis applies thematic coding to communicative elements such as narrative framing, symbolic language, relational interaction, and meaning negotiation, identifying key themes of meaning-making, authority, narrative construction, and relationality. The findings demonstrate that ruqyah functions not merely as a spiritual ritual but as a symbolic and relational communicative process through which meanings of illness, hope, and acceptance are constructed. From a communication studies perspective, ruqyah operates as therapeutic communication in which meaning is co-constructed through religious narratives, interpersonal interaction, and faith-based symbolic language that frame experiences of suffering and healing. These processes help individuals reinterpret illness and strengthen psychological resilience within religious contexts. This study contributes to health communication scholarship by conceptualizing ruqyah as a communicative meaning-making practice rather than solely ritual healing. It further advances Islamic Studies by extending the concept of religious coping through a communicative perspective, highlighting the continuing relevance of Islamic healing practices within increasingly medicalized social environments.